New Lexical and Phraseological Faunal Units in the Language Observatory of the University of Warsaw from a Cross-Linguistic Polish-English Perspective - Szerszunowicz, Joanna (Poznańskie Studia Slawistyczne, 2021)
The aim of the present paper is to discuss the new Polish faunal lexical and phraseological units from a cross-linguistic perspective. The research corpus is compiled on the basis of Obserwatorium Językowe Uniwersytetu Warszawskiego (the Language Observatory of the University of Warsaw) – an online source containing the items which are in use and which have not been included in dictionaries so far. The English equivalents allocated for these units are analysed and divided into four groups: quasi-absolute, partial, parallel and zero counterparts.